Pengaruh Takaran Bahan Organik Terhadap Pertumbuhan dan Hasil Tanaman Kubis Bunga (Brassica oleracea L. var. botrytis sub var. cauliflora DC) Pada Dua Sistim Pengairan Yang Berbeda Di Dataran Rendah - Netti Nurlenawati; Rommy Andhika Laksono (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2022)
The study was aimed to determine and analyze the effects of organic material on the cauliflower (Brassica oleracea L. var . botrytis sub var. cauliflora DC ) in different irrigation systems during dry season in the lowlands. This experiment was conducted in paddy fields in the village of Sukapura, Rawamerta Karawang from May to August 2021. The experimental design was Split Plot Design. As the main plot was the irrigation system (A), consisted of two levels: (1) a1 = furrow irrigation, and (2) a2 = sprinkler irrigation (manual). The split plot was the dose of organic material (B), consisted of 4 levels: (1) b0 = no organic material (cow manure 0 t ha-1), (2) b1 = cow manure 5 t ha-1, (3) b2 = cow manure 10 t ha-1, and (4) b3 = cow manure 15 t ha-1. Each treatment was repeated four times. The results showed that there were significant interaction between irrigation systems and the dose of organic matter on the number of leaves at 14 days after planting (dap), stem diameter at 28 days after planting, height curd and weight curd. There were not any effects from irrigation systems on the growth and yield of cauliflower. There were effects from the dose of organic material on growth and yield of cauliflower. The dose of cow manure at 15 t ha-1 gave the highest growth and yield of curd with leaves weight 936.13 g, total yield of 18.34 kg per plot equivalent to 30.57 t ha-1 and marketable yield per plot is 16.81 kg equivalent to 28.02 t ha-1.